2015
DOI: 10.1590/0104-07072015003620012
|View full text |Cite
|
Sign up to set email alerts
|

Everyday life of women with a history of domestic violence and abortion

Abstract: This is a qualitative study based on the Comprehensive Sociology. Aimed to understand the daily life of women with a history of domestic violence who had an abortion. We conducted in-depth interviews with ten women who were admitted to the hospital for abortion and reported experiencing domestic violence. Mostly characterized by being black, low education, between 18 and 40 years. The process of organizing and analyzing the data was based on the notions of Comprehensive Sociology and theoretical sensitivity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Entretanto, esse dado pode refletir tanto uma limitação do estudo documental quanto o receio das mulheres frente à ilegalidade de realização de aborto no Brasil. Entende-se, então, que a taxa de abortamentos induzidos pode estar subestimada, assim como sugerido em outros estudos (12,13) .…”
Section: Discussionunclassified
“…Entretanto, esse dado pode refletir tanto uma limitação do estudo documental quanto o receio das mulheres frente à ilegalidade de realização de aborto no Brasil. Entende-se, então, que a taxa de abortamentos induzidos pode estar subestimada, assim como sugerido em outros estudos (12,13) .…”
Section: Discussionunclassified
“…According to research in a public maternity hospital in Salvador, Bahia, domestic violence was identified as a determining factor in the decision to abort, and, according to reports of the study participants, the behavior of the partner changed after the discovery of pregnancy, with the increase of marital conflicts, which culminated in the decision to abort. 26 Another study 19 on the experience of abortion and a bioethical approach shows that gender-specific violence, domestic violence, causes changes in sexuality, not only by physical violence, but also by conjugal sexual violence, which in many cases is not recognized as such. Sexual violence can expose women to sexual and psychological problems and the risk of contracting sexually transmitted infections.…”
Section: Discussionmentioning
confidence: 99%
“…Remete à noção de espacialidade, em que o mundo é permeado por conflitos, ódio e amores, resultando em um lugar dinâmico, podendo ser chamado de socialidade. Ao oferecer diferente visão sobre as relações humanas, o presente referencial contribui às pesquisas científicas (19) , especialmente da área de Enfermagem, a qual é imprescindível compreender como cada pessoa vivencia o processo saúde-doença.…”
Section: Métodounclassified